X is equal to 2. you can set them equal to each other because they are corresponding angles, which means they are congruent.
For this case we must solve each of the functions.
We have then:
f (x) = x2 - 9, and g (x) = x - 3
h (x) = (x2 - 9) / (x - 3)
h (x) = ((x-3) (x + 3)) / (x - 3)
h (x) = x + 3
f (x) = x2 - 4x + 3, and g (x) = x - 3
h (x) = (x2 - 4x + 3) / (x - 3)
h (x) = ((x-3) (x-1)) / (x - 3)
h (x) = x-1
f (x) = x2 + 4x - 5, and g (x) = x - 1
h (x) = (x2 + 4x - 5) / (x - 1)
h (x) = ((x + 5) (x-1)) / (x - 1)
h (x) = x + 5
f (x) = x2 - 16, and g (x) = x - 4
h (x) = (x2 - 16) / (x - 4)
h (x) = ((x-4) (x + 4)) / (x - 4)
h (x) = x + 4
√x + 11=15 x=16
√x= 15-11 x=16
Answer:
(s-t)(-1) = -1
(s+t)(-1) = -7
Step-by-step explanation:
Given the following set of functions
s(x)=2x-2
t(x)=3x
(s-t)(x) = s(t) - t(x)
(s-t)(x) = 2x - 2 - 3x
(s-t)(x) = -x -2
(s-t)(-1) = -(-1) - 2
(s-t)(-1) = 1-2
(s-t)(-1) = -1
(s+t)(x) = s(t) + t(x)
(s+t)(x) = 2x - 2 + 3x
(s+t)(x) = 5x -2
(s+t)(-1) = 5(-1) - 2
(s+t)(-1) = -5-2
(s+t)(-1) = -7